Nonalcoholic fatty liver disease: cause or consequence of insulin resistance? - Ekaterina E. Mishina; Alexander Y. Mayorov; Pavel O. Bogomolov; Maria V. Matsievich; Ksenia Y. Kokina; Apollinariya V. Bogolyubova (Сахарный диабет)
Nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM) are pathological conditions that are co-occurring, and have been reaching epidemic proportions. One of the most significant risk factors for the development of both T2DM and NAFLD is obesity, which increases existing insulin resistance (IR). IR thought to be one of the main pathogenic causes linking T2DM and NAFLD. In recent years, there has been increased interest in obtaining non-invasive methods for assessing fibrosis and determining indications for liver biopsy, such as the NAFLD fibrosis score, extended liver fibrosis panel, and transient elastography. However, liver biopsy remains the gold standard for diagnosing NAFLD. Given that patients with T2DM are at higher risk of NAFLD than the general population, and that the presence of diabetes is a risk factor for the progression of NAFLD, patients with T2DM should be more closely monitored by clinicians. The present review paper is devoted to the search for cause–effect relationships of concurrent diseases such as NAFLD and disorders of carbohydrate metabolism, and priority areas of diagnosis of NAFLD.